2003
DOI: 10.1002/uog.901
|View full text |Cite
|
Sign up to set email alerts
|

Single umbilical artery at 11–14 weeks' gestation: relation to chromosomal defects

Abstract: Objective To determine the possible association between single umbilical artery (SUA) at 11-14 weeks of gestation and the incidence of chromosomal abnormalities. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
3
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 29 publications
1
46
3
8
Order By: Relevance
“…The incidence of SUA has been reported to vary from 0.5% to 2.5% among healthy neonates and from 9% to 11% among aneuploid and aborted fetuses. 13 Furthermore, an SUA diagnosed at 11 to 14 weeks' gestation has a high association with chromosomal defects 14 and has also been associated with congenital malformations of the heart and gastrointestinal, renal, and central nervous systems. 15 There are differing conclusions with regard to its relationship to FGR, but most reports indicate that if Doppler studies of the UA show no abnormalities, the risk of FGR is low.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SUA has been reported to vary from 0.5% to 2.5% among healthy neonates and from 9% to 11% among aneuploid and aborted fetuses. 13 Furthermore, an SUA diagnosed at 11 to 14 weeks' gestation has a high association with chromosomal defects 14 and has also been associated with congenital malformations of the heart and gastrointestinal, renal, and central nervous systems. 15 There are differing conclusions with regard to its relationship to FGR, but most reports indicate that if Doppler studies of the UA show no abnormalities, the risk of FGR is low.…”
Section: Discussionmentioning
confidence: 99%
“…The sonograpic diagnosis can be made either by visualizing a transverse section of a free loop of the cord or by using color Doppler to identify both arteries on both sides of the bladder in a longitudinal section of the abdomen. Using the latter method has the benefit of indentifying which side is missing [15]. The diameter of the cord with only two vessels tends also to be larger than a three vessel cord as well, with a diameter of > 4 mm or a vein/artery ration of < 2 perhaps being diagnostic of SUA [15].…”
Section: Single Umbilical Arterymentioning
confidence: 99%
“…Using the latter method has the benefit of indentifying which side is missing [15]. The diameter of the cord with only two vessels tends also to be larger than a three vessel cord as well, with a diameter of > 4 mm or a vein/artery ration of < 2 perhaps being diagnostic of SUA [15]. Lastly, multiple segments should be examined to exclude fusion of the two arteries.…”
Section: Single Umbilical Arterymentioning
confidence: 99%
“…21 Associated congenital anomalies in a fetus with SUA confer increased risk of aneuploidy estimated to be 31%.…”
Section: Diagnosismentioning
confidence: 99%
“…The increased morbidity and mortality associated with pregnancies complicated by SUA is attributable to increased rates of associated anomalies and aneuploidy. 21 In a very recent publication by Dagklis et al they showed that the finding of SUA should prompt the sonographer to search for fetal defects and if these are found the risk for chromosomal abnormalities is increased. In cases of apparently isolated SUA there is no evidence of increased risk of chromosomal abnormalities.…”
Section: Diagnosismentioning
confidence: 99%